Blended Instruction in Elementary Mathematics: Effects of Demonstration Method and Digital Media on Calculation Skills - Agung Yunianto; Banun Havifah Cahyo Khosiyono; Berliana Henu Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Basic calculation skills—addition, subtraction, multiplication, and division—are foundational in elementary mathematics. However, many students struggle to master these skills using traditional instruction alone. This study explores the effectiveness of integrating the demonstration method with digital learning media to improve calculation skills among Grade IV elementary students. A one-group pretest-posttest quasi-experimental design was employed with 40 fourth-grade students from Mendak State Elementary School, Indonesia. The intervention combined step-by-step teacher-led demonstrations with digital tools, such as interactive apps, over an eight-week period (16 sessions). Students’ calculation abilities were measured before and after the intervention using a validated 20-item multiple-choice test. Data were analyzed using paired samples t-tests after confirming normality through the Kolmogorov-Smirnov test. Students showed significant improvement in posttest scores (M = 85.56) compared to pretest scores (M = 60.62), with a mean gain of 24.95 points (t = 15.43, p 0.001). Most students shifted from “fair” or “low” to “high” or “very high” proficiency categories. Female and older students exhibited slightly higher gains, though improvements were consistent across all demographics. The integration of structured demonstration with digital media significantly enhanced students’ arithmetic performance. The blended approach leveraged the clarity of modeling with the engagement and personalization of digital tools. Despite the study’s limitations—such as the absence of a control group—findings support the use of blended instructional methods in elementary mathematics.